Are Increasing Earnings Associations between Partners of Concern for Inequality? A Comparative Study of 21 Countries. (6th January 2022) - Boertien, Diederik; Bouchet-Valat, Milan
Abstract: Partners increasingly resemble each other in terms of earnings across Western countries. These increases in earnings similarity are often considered to be drivers behind growing income inequality between households. We argue that increases in earnings similarity do not necessarily lead to augmented inequality between households. Their overall effect depends on whether and how the processes that increase earnings similarity affect inequality through other pathways. Using data from the Luxembourg Income Study on 21 countries, we decompose changes over time in earnings inequality. We show that even though the correlation in earnings between partners increased in most countries, this only amplified inequality on some occasions. In several countries, increases in the earnings correlation are driven by general changes in employment rates. Given that these increases in employment equalized earnings across households through other pathways, the inherently connected increases in the earnings correlation are of less concern from an inequality perspective. In other countries, where increases in earnings similarity are produced by augmented similarity in earnings among dual-breadwinner couples or by selective changes in employment, increases in earnings similarity are of more concern for inequality between households.